Maternal and Adolescent Factors Associated with Menstrual Hygiene of Girls in Senior Secondary Schools in Lagos, Nigeria - Rasheed, Tajudeen Olusegun; Afolabi, Wasiu Adebowale (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: